Analisis Sistem Drainase Sepanjang 3,2 Km Di Kawasan Jl.Sederhana Tembung Pasar 7 Medan - Siburian, Hemat Grasella; Siburian, Ezy Hesekiel; Simanjuntak, Rizky (Jurnal Ilmu Teknik Sipil Indonesia, 2026)
This study analyzes the performance of a 3.2 km drainage system in the Jl. Sederhana Tembung Pasar 7 area, Medan City, in accommodating rainfall runoff and domestic wastewater. The methods used include field observation, geometric population projection, rainfall analysis, and runoff discharge calculation using the Rational Method. The results show an average rainfall of 204.17 mm/month, classified as moderate to high. Population growth increases domestic wastewater discharge up to 1,896.48 m³/day (100-year projection). The drainage capacity of 5,760 m³ is reduced due to sedimentation and waste accumulation. The runoff discharge of 1.55 m³/second may exceed capacity during heavy rainfall. Therefore, the drainage system is not yet optimal and requires capacity improvement and regular maintenance.